2018 Joint European consensus document on the management of antithrombotic therapy in atrial fibrillation patients presenting with acute coronary syndrome and/or undergoing percutaneous cardiovascular interventions: a joint consensus document of the European Heart Rhythm Association (EHRA), European Society of Cardiology Working Group on Thrombosis, European Association of Percutaneous Cardiovascular Interventions (EAPCI), and European Association of Acute Cardiac Care (ACCA) endorsed by the Heart Rhythm Society (HRS), Asia-Pacific Heart Rhythm Society (APHRS), Latin America Heart Rhythm Society (LAHRS), and Cardiac Arrhythmia Society of Southern Africa (CASSA). Issue 2 (21st July 2018) - Lip, Gregory Y H; Collet, Jean-Phillippe; Haude, Michael; Byrne, Robert; Chung, Eugene H; Fauchier, Laurent; Halvorsen, Sigrun; Lau, Dennis; Lopez-Cabanillas, Nestor; Lettino, Maddalena; Marin, Francisco; Obel, Israel; et al.
Abstract: In 2014, a joint consensus document dealing with the management of antithrombotic therapy in atrial fibrillation (AF) patients presenting with acute coronary syndrome (ACS) and/or undergoing percutaneous coronary or valve interventions was published, which represented an effort of the European Society of Cardiology Working Group on Thrombosis, European Heart Rhythm Association (EHRA), European Association of Percutaneous Cardiovascular Interventions (EAPCI), and European Association of Acute Cardiac Care (ACCA) endorsed by the Heart Rhythm Society (HRS) and Asia-Pacific Heart Rhythm Society (APHRS). Since publication of this document, additional data from observational cohorts, randomized controlled trials, and percutaneous interventions as well as new guidelines have been published. Moreover, new drugs and devices/interventions are also available, with an increasing evidence base. The approach to managing AF has also evolved towards a more integrated or holistic approach. In recognizing these advances since the last consensus document, EHRA, WG Thrombosis, EAPCI, and ACCA, with additional contributions from HRS, APHRS, Latin America Heart Rhythm Society (LAHRS), and Cardiac Arrhythmia Society of Southern Africa (CASSA), proposed a focused update, to include the new data, with the remit of comprehensively reviewing the available evidence and publishing a focused update consensus document on the management of antithrombotic therapy in AF patients presenting with ACS and/or undergoing percutaneous coronary or valve interventions, and providing up-to-date consensus recommendations for use in clinical practice.